An analytical study on sublimation process in the presence of convection effect with heat and mass transfer in porous medium - Jitendra; Rai K.N.; Singh J. (My University, 2025)
The mathematical study of one dimensional heat and mass transfer phenomena is investigated. A Stefan like phenomena is defined as a heat and mass transfer problem with presence of convection in vapour region for heat and moisture flow and convective term due to mass transfer of the water vapour in frozen region. The sublimation process considered in two region: (i) In frozen region, s(t)< x < ∞, there is no effect of moisture in this region. (ii) In vapour region, 0 < x < s(t), there is an effect of heat and moisture flows. The thermo-physical properties of each region are constant, but may be differ for different region. The analytical solutions are obtained for the temperature and moisture profile and moving sublimation interface by using the similarity transformation procedure. The effect of some parameters included in the sublimation process with various enclosures, i.e. dimensionless quantity l0, Peclet number Pe, Luikov number Lu, KT, a21 and other constant parameters are comprehensively investigated and represented graphically. © 2021 Elsevier Ltd